2019
DOI: 10.1016/j.pedn.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Families in Paediatric Oncology Nursing: Critical Incidents From the Nurses' Perspective

Abstract: PURPOSE: Paediatric oncology nurses encounter challenges with families on a daily basis. This study explores how nurses describe significant incidents when encountering families and family members during the child's hospitalisation in the paediatric oncology unit. DESIGN AND METHODS: A qualitative study with a phenomenological approach in which 17 paediatric oncology nurses from three different hospitals described critical incidents related to families. The participants' written descriptions were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…Our results describe lack of resources, compared to prior findings, 9,10 and unfortunately, they mirror the worldwide situation in nursing with heavy workloads and nursing shortages. 37 Recently, Hopia and Heino-Tolonen 38 described that busy work shifts caused concerns among paediatric oncology nurses, as a lack of time stopped them from supporting families in a way they felt was needed. Similarly, Newman et al 39 reported that failing to provide compassionate, high-quality care escalated moral distress among paediatric oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Our results describe lack of resources, compared to prior findings, 9,10 and unfortunately, they mirror the worldwide situation in nursing with heavy workloads and nursing shortages. 37 Recently, Hopia and Heino-Tolonen 38 described that busy work shifts caused concerns among paediatric oncology nurses, as a lack of time stopped them from supporting families in a way they felt was needed. Similarly, Newman et al 39 reported that failing to provide compassionate, high-quality care escalated moral distress among paediatric oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all nurses perceived it as highly disturbing to give in to the family's demand not to discuss death with a dying child who asks about it. Although parents and nurses may share a desire to protect the child by concealing the harsh truth or by using white lies (Shali et al., 2020 ), the distressing impact of limited truth‐telling is well established in qualitative studies (Hopia & Heino‐Tolonen, 2019 ; Testoni et al., 2020 ). Consistent with earlier results (Ventovaara et al., 2021 ), nurses in this study did not experience this situation very often.…”
Section: Discussionmentioning
confidence: 99%
“…Forced procedures cause ethical concerns for paediatric nurses, especially when the procedure increases the suffering of the child in situations with a little hope of cure or if the nurse disagrees with the necessity of the procedure (Bartholdson et al., 2015 ). Another ethical problem related to paediatric decision‐making occurs when young patients are not allowed to hear the truth about their illness (Bartholdson et al., 2015 ) or their imminent death (Hopia & Heino‐Tolonen, 2019 ). The patient advocacy is an essential part of the paediatric nurses’ role and situations that make it difficult to adhere to the wishes of the children, can be morally distressing.…”
Section: Introductionmentioning
confidence: 99%
“…Hastalığın nüks etme, çocuğun geç etkilere maruz kalma ya da hayatını kaybetmesi gibi olası durumlara yönelik hazırlıklı olması oldukça önemlidir (62) . Hemşireler 24 saat boyunca çocuklara bakım sağlayıcı ve ebeveynler ile hastalar için ilk temas noktası olduğundan oldukça önemli bir konumdadır (63) . Son dönemde bu özel grupta aile merkezli hemşirelik bakımı sağlamanın yararlarına ilişkin vurgu yapılmaktadır.…”
Section: Discussionunclassified